Use of mandibular advancement devices for obstructive sleep apnoea treatment in adults - Chaves Jr., Cauby Maia (2017)
Introduction: This article is based on Clinical Guidelines for obstruc - tive sleep apnoea (OSA) established by a taskforce coordinated by the Brazilian Sleep Association. Objective: The aim of this article is to evaluate the available scien - tific evidence regarding the efficacy, adherence and safety of using mandibular advancement devices (MAD) as a therapeutic course for treating obstructive sleep apnoea in adult patients. Method: Active searches were performed in the PubMed/MEDLINE, EMBASE, Scielo/LILACS and Cochrane Library databases. Methodolo - gical aspects were used to rank the levels of evidence according to the criteria of the Centre for Evidence-Based Medicine at Oxford. Results: Mandibular advancement devices offer the best results for patients with primary snoring, upper airway resistance syndrome and mild or moderate OSA (Levels of Evidence I and II). Continuous positive airway pressure (CPAP) is more effective in controlling OSA (Level of Evidence I). However, patients seem to exhibit greater adherence to oral appliances (MAD) than (CPAP) devices. The long-term side effects most observed after the use of MADs are related to changes in the mandibular and dental positions (Levels of Evidence I and II). Conclusion: MAD constitute a therapeutic alternative for OSA and promote favourable results with good efficacy and adherence to treatment. Side effects can arise in the short, medium or long term. Patients must be informed about the possible occurrence of these adverse effects, and the orthodontist must be able to manage any side effects that occur due to the use of these devices.